Clinical researchThe cardio-renal-anaemia syndrome predicts survival in peritoneally dialyzed patients - Malyszko, Jolanta; Zbroch, Edyta; Malyszko, Jacek; Mysliwiec, Michal; Iaina, Adrian (Archives of Medical Science, 2010)
Introduction : Anaemia is one of the arms of the cardio-renal-anaemia syndrome (CRA) in chronic kidney disease (CKD) patients. The correction of anaemia was effective in the amelioration of both cardiac and renal failure. We studied the relationship between the severity of CRA syndrome in peritoneally dialyzed patients and their survival probability. Material and methods: Fifty-six patients on peritoneal dialysis were followed for 1 year. Definition of the severity of the CRA in dialysis patients: cardiac arm – NYHA class I-IV = 1-4 points, renal arm – non-diabetic patients age 65 = 2 points, diabetic patients age 65 = 4 points, anaemia arm – Hb 11-13 g/dl (male), 11-12 g/dl (female) = 1 point, Hb 10-11 g/dl = 2 points, Hb 9-10 g/dl = 3 points, Hb < 9 g/dl = 4 points. The severity score = cardiac + renal + anaemia arms score divided by 3 (maximum 4 points). Results: A total of 10/56 patients (18%) died during the study. The median value for the severity score of the whole group was 1.69. In Kaplan-Meier analysis CRA severity score was strongly associated with mortality (p < 0.001). It also correlated with albumin, CRP, erythropoietin treatment, Hb and fasting glucose. In the multivariate regression analysis age, Hb, albumin, and presence of diabetes remained significant predictors of death. Conclusions: The severity score of CRA syndrome in peritoneally dialyzed patients is an independent and very significant predictor of death. The patients with a high severity score had more hypoalbuminaemia, higher inflammation markers and higher prevalence of diabetes and chronic heart failure. Cardio-renal-anaemia syndrome severity scoring as defined by us could be an easy tool to predict outcome of dialysis patients.